Arthroscopic all-inside ACL reconstruction with anterolateral tendon fixation: a prospective cohort study on restoring rotational stability in high-grade tibial shift - Gu, Haoran; Niu, Aifang; Ji, Jingrui; He, Miao; Yang, Ying; Lu, Junxia; Lv, Jianghong; Yi, Yongdong; Zhou, Hui; Zhou, Wuping (Frontiers in Surgery, 2025)
AimThis study aimed to evaluate the early efficacy of combined all-inside anterior cruciate ligament (ACL) reconstruction and anterolateral tendon fixation in addressing knee instability associated with ACL rupture and high-grade anterior tibial translation (≥10 mm).MethodsIn this prospective cohort study, 21 patients (16 men, 5 women; mean age: 27.4 ± 5.8 years) with ACL rupture and grade III anterior tibial displacement were selected from 90 consecutive cases treated between January 2019 and January 2020. All procedures were performed by a single surgeon using autologous semitendinosus tendon grafts (diameter: 8–9 mm). The all-inside ACL reconstruction was augmented with anterolateral tendon fixation utilizing the posterior fibers of the iliotibial band. Postoperative evaluations were conducted at immediate, 1-, 3-, 6-, and 12-month intervals and included: objective stability testing (Lachman and pivot-shift tests), functional outcome assessments (IKDC, Lysholm, and KOOS scores), and radiographic measurement of anterior tibial displacement.ResultsAll patients completed at least 12 months of follow-up, with no reported cases of recurrent instability. Immediate postoperative assessments revealed negative Lachman and pivot-shift tests in 100% of patients, indicating restored knee stability. At the 12-month follow-up, 90.5% (19/21) of patients maintained full stability, while the remaining two exhibited only grade I laxity, representing a significant improvement from preoperative grade III instability (P < 0.001). Functional outcomes also improved markedly, with mean IKDC scores increasing from 48.6 ± 10.3 preoperatively to 86.7 ± 3.6 at 12 months (P < 0.001), and Lysholm scores rising from 52.6 ± 12.4 to 89.6 ± 2.9 (P < 0.001). At final follow-up, 52.4% (11/21) of patients achieved “excellent” and 38.1% (8/21) “good” ratings on the Lysholm scale (P < 0.001 vs. baseline). Additionally, KOOS subscale analysis demonstrated significant pain reduction, with scores improving from 45.2 ± 9.1 preoperatively to 88.3 ± 4.7 postoperatively (P <  0.001).ConclusionCombined all-inside ACL reconstruction and anterolateral tendon fixation could effectively restore anterior and rotational stability in knees with ACL rupture and high-grade tibial displacement. Early outcomes demonstrate promising functional recovery and objective stability at short-term follow-up, suggesting that this technique may offer biomechanical benefits for managing severe instability patterns. However, long-term studies are needed to confirm the durability of these results.